In vitro Evaluation of Tribocorrosion Induced Failure Mechanisms at the Cell‐Metal Interface for the Hip Implant Application1 . Issue 5 (10th March 2017) - Runa, Maria; (Jenny) Lau, Eik‐lang; Takoudis, Christos; Sukotjo, Cortino; Shokuhfar, Tolou; Rocha, Luis; Mathew, Mathew
Abstract : In a hip joint environment, the bone‐metal implant interface of an implant is exposed to the combined effect of wear and corrosion (tribocorrosion). This may create mechanical instability and cause early failure of the implants. The aim of this work was to investigate the tribocorrosion behavior of Ti6Al4V alloys in the presence of bone‐forming cells cultured on its surface (cell‐metal interface), using an electrochemical and tribological approach. The results showed that at a cathodic potential (−0.9 V), the presence of osteoblast‐like cells and serum proteins in the media might induce a higher passivation rate of the oxide film, enhancing the corrosion resistance. However, when the surface is in steady state (0.7 V) they show a lower resistant to corrosion, increasing the susceptibility to corrosion. Abstract : This work reports the interactions of the femoral stem part of the hip implants with the bone cells, the bio‐tribocorrosion testing methods. This findings may contribute to a better understanding on the reason why physicians advise their orthopedic patients to have some level of physical activity after the surgery.